Monumen Nasional: Symbols of Authority and Modernity in Jakarta's Development from 2012 to 2022 - Tomy Wijaya; Yusuf, Syafruddin (ASANKA : Journal of Social Science and Education, 2025)
This study examines the National Monument (Monas) as a dynamic symbolic structure that reflects shifting configurations of state authority and urban modernity in Jakarta from 2012 to 2022. The research is grounded in the premise that urban monuments in postcolonial cities function not only as historical markers but also as political instruments that articulate national identity and territorial power. The study aims to trace the historical evolution, symbolic transformations, and spatial politics surrounding Monas within the broader context of Jakarta’s development. Employing a historical method combined with a symbolic–critical qualitative approach, data were collected from state documents, archival records, city planning maps, photographic documentation, and media reports. The findings reveal that the meaning of Monas has transitioned from a revolutionary symbol under Sukarno to a contested urban icon shaped by modernization, revitalization policies, and shifting political agendas. These transformations highlight tensions between heritage preservation, state authority, and contemporary urban aesthetics. The study contributes to understanding how public monuments generate political meaning and how urban spaces become sites of negotiation between the state and society. It concludes by emphasizing the need for participatory and interdisciplinary approaches in future research on public space and symbolic landscapes.